Hazard and Lag Effect of Compound Heat-Drought Events in Southeastern Coastal China under Climate Change Scenarios - An Aohua; Chen Jie; Gao Guoping (Redai dili)
Southeastern coastal China is sensitive to climate change and is characterized by an advanced economy and aging population. The region faces substantial exposure and vulnerability under climate change, making it a potential hotspot for Compound Heat-Drought Events (CHDEs). Therefore, in this study, we used multi-model integrated prediction data from the Coupled Model Intercomparison Project Phase 6 (CMIP6) to simulate different climate change scenarios, along with the standardized precipitation evapotranspiration index (SPEI), sliding threshold method, and Copula joint probability distribution to define drought, heat, and compound events, respectively. Additionally, we aimed to analyze the temporal and spatial patterns of future CHDE hazards in southeastern coastal China under various climate change scenarios (SSP1-2.6, SSP2-4.5, SSP3-7.0, and SSP5-8.5) and during different periods (2021-2040, 2041-2060, and 2081-2100). To further understand the lag effect of heat events on drought, we applied a lagged logistic regression model to quantify the attributable fraction (AF) for delays ranging from 1 to 7 days. In particular, we used the CN05.1 high-resolution gridded daily observation dataset to compare and analyze CMIP6 model prediction data, verifying their applicability to the study area and the accuracy of the prediction results. Our results indicate that CHDE hazards (number of occurrence days, intensity, and duration) in southeastern coastal China are expected to increase in the future, with a faster increase under the SSP5-8.5 scenario than under the SSP1-2.6, SSP2-4.5, and SSP3-7.0 scenarios. The intensity is projected to increase faster than the number of occurrence days and duration. Under the SSP5-8.5 scenario, the CHDE intensity at the end of the 21st century is projected to reach 3.41 times that during the baseline period (1995-2014), while the corresponding occurrence days and duration are projected to be 1.74 and 1.61 times those of the baseline period, respectively. This indicates that the probability of high-intensity CHDEs is expected to increase significantly considerably in the future. As for the spatial pattern, the spatial heterogeneity of the hazards (occurrence day, intensity, and duration) was more pronounced under the SSP5-8.5 scenario than under the other scenarios, especially during 2081-2100. Under the SSP5-8.5 scenario, the combined hazard indexes exceed 0.6 in southeastern Fujian, eastern Zhejiang, Jiangsu, and Shanghai, with some areas having indexes as high as 0.9. Spatial variability was shaped by factors such as distance from the coastline, availability of water resources, land use patterns, and human activities. Notably, the spatial heterogeneity in the CHDE duration was significantly greater than that in the occurrence days and intensity. Under the SSP5-8.5 scenario, the CHDE duration was approximately 2.23 times higher in the high-value areas than in the low-value regions, whereas the differences in occurrence days and intensity were smaller, at 1.13 and 1.11 times, respectively. This highlights the urgent need for regional adaptation strategies that focus on the persistence of CHDEs. The lagged effect of heat on drought events in southeastern coastal China exhibits an east-west sea-land gradient, with differences between the northern and southern areas. Specifically, the lag effect gradually intensifies from the inland to coastal regions. This may be attributed to the fact that coastal regions are influenced by the combined impact of heat on both the land and ocean and are more likely to experience delayed droughts. In the north-south divergence, northern Jiangsu experienced a stronger influence of heat on subsequent droughts than the other areas. This is primarily because of its predominantly dryland environment, which is highly vulnerable and in which heat events are more likely to trigger drought events. Under the SSP5-8.5 scenario, the AF value exceeded 5% in the northeastern Jiangsu coastline, eastern Zhejiang coastline, and Shanghai, with lag times of up to 7 days in some areas. This indicates that heat events will have a prolonged effect on subsequent droughts. These results provide a scientific foundation for policymakers to formulate effective disaster prevention and mitigation strategies tailored to their regional needs. Furthermore, they support decision making to promote a climate-adapted society and contribute to sustainable development.